Implementasi Model Konseptual Pemetaan Potensi Konflik di Ditintelkam Polda Jateng dengan Agile - Ardiawan Bagus Harisa; Jeremyas Cornelis Abigail Wihardjono; Augusta Steven Benedict (Jurnal ICT: Information Communication & Technology, 2021)
The performance of the Directorate of Police Intelligence and Security is judged by how capable they are in reducing potential conflicts that may occur or conflicts that have occurred. The better performance of the police in carrying out early detection of potential conflicts will result in the peace and security of the public can be maintained. The potential conflicts detection system can be used to improve the performance of police officers in reducing the potential conflicts that may occur. The performance of the potential conflicts detection activity can be improved by observing the database at the Directorate of Intelligence and Security of the Central Java Regional Police which contains information and reports of potential conflicts that have been detected early as well as conflicts that have occurred. In addition, the various supporting features such as graphic visualization to display the data that is being observed is useful to shorten the decision-making time, therefore the prevention and control of potential conflicts can be resolved more quickly